2000
DOI: 10.1002/chin.200042176
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Sesquiterpenoids from Scorzonera hispanica L.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Additionally, S. latifolia aerial part extract displayed notable activity. one-acetate (15), and olean-12-en-11-one-3-acetyl (16)] were also tested for their inhibitory effects on the TNF-α and IL-1β production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, S. latifolia aerial part extract displayed notable activity. one-acetate (15), and olean-12-en-11-one-3-acetyl (16)] were also tested for their inhibitory effects on the TNF-α and IL-1β production.…”
Section: Resultsmentioning
confidence: 99%
“…From the above mentioned, we suggested that chlorogenic acid (8), derivatives of dicaffeoyl-quinic acid (6 and 7), and flavonoids, especially quercetin-3-O-β-D-glucoside (1) and hyperoside (2) could be responsible for the anti-inflammatory activity of tested extracts. Therefore, further experiments were carried out with phenolic compounds previously obtained from Scorzonera species (1)(2)(3)(4)(5)(6)(7)(8), to assay the inhibition of TNF-α and IL-1β production in THP-1 cells, and later also with triterpenes 9-16, because taraxasterol acetate (9) isolated from S. latifolia showed previously analgesic activity in vivo in writhing and tail-flick tests [21] and also other triterpenoid substances like lupeol derivatives (10 and 11), β-sitosterol (12) and other triterpenes (13)(14)(15)(16) could potentially demonstrate anti-phlogistic effect [38,39]. Unfortunately, only weak activity of compounds tested was observed, and no statistically significant activity has been observed in comparison with standard used (prednisone, Supplementary Materials, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biologically active substances contained in the tissues of S. hispanica, e.g., inulin [12,13], sesquiterpenoids including bisabolane [14][15][16], lignans including syringaresinol [16,17], polyphenols such as flavonoids and phenolic acids [16], may play a role in the prevention and treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%